Disorders of Puberty The Causes and the Endocrine Medical Treatment - La Vignera, Sandro; Calogero, Aldo E. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
How often is male idiopathic infertility diagnosed nowadays? It is estimated that 70% of male infertility is apparently idiopathic because its etiology cannot be found despite a complete diagnostic procedure. Epidemiological studies have highlighted that sperm concentration and total count have halved in the past forty years. The reasons for this decline are still unknown and, therefore, it is urgently necessary to research the etiopathogenetic moments. Given that Sertoli cells are responsible for supporting spermatogenesis, much attention should be focused on their function. During childhood, these cells have peculiar characteristics. After the onset of puberty, they reach a state of maturity and lose their ability to proliferate. Therefore, several environmental or lifestyle factors in childhood could reasonably interfere with the proliferation of Sertoli cells and this may be the cause of so-called idiopathic infertility in adulthood. For that reason, this book explores molecular aspects involving prepubertal Sertoli cells, risk factors for infertility in the early stages of life, and the correct management of andrological health from the first months of life and during infancy and adolescence. A close collaboration between pediatricians, endocrinologists, and andrologists is of fundamental importance to achieve an important goal: To protect the health of the fathers of tomorrow!